ATP13A2 restrains macrophage NLRP3 inflammasome activation to repress neurodegeneration via modulating mitochondrial homeostasis - Ziqi Zou; Jiajie Zhou; Yanhua Lu; Yuting Huang; Linru Zhou; Xiaoyu Wang; Jiahui Chen; Hengrui Tian; Xinnuo Ge; Chenyao Guo; Weiran Yao; Xiaosheng Zheng; et al. (Proceedings of the National Academy of Sciences, 2026)
Neuro-immune crosstalk is increasingly recognized in Parkinson’s disease (PD), and ATP13A2 is well known for its neuroprotective role. However, it remains unclear whether ATP13A2 mutations carried by PD patients contribute to immune dysfunction that exacerbates disease progression. Here, we systematically demonstrate that many ATP13A2 mutations result in a loss-of-expression phenotype. ATP13A2 is highly expressed in macrophages. Myeloid ATP13A2 deficiency causes uncontrolled NLRP3 inflammasome activation driven by lysosomal alkalization and subsequent disrupted mitochondrial homeostasis, rendering mice susceptible to a PD-like phenotype. PD-linked ATP13A2 loss-of-expression mutants fail to restore the ATP13A2 levels required to suppress NLRP3 hyperactivation in ATP13A2-depleted human THP-1 monocytes. Macrophages from a PD patient carrying the ATP13A2 loss-of-expression L927P mutation exhibit excessive NLRP3 activation due to lysosomal-mitochondrial dysfunction. Our findings provide insight into PD pathogenesis, emphasizing genetic factor-driven dysregulated macrophage NLRP3 activation, particularly in ATP13A2 loss-of-expression mutation cases.